2020
DOI: 10.1097/hjh.0000000000002736
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of SBP at home by parents using hand-held Doppler device and aneroid sphygmomanometer: a single-centre experience

Abstract: Objective: We taught parents to use at home a hand-held Doppler device and aneroid sphygmomanometer for SBP measurement (HDBPM).Methods: Retrospective study including all children referred to evaluate hypertension over a 6-year period. Each child underwent HDBPM measurements performed by parents while awake over 2 weeks with three measurements performed twice daily.Results: Of n ¼ 155 children, 145 (93.5%) were successful and aged median (interquartile range) 2.48 (1.01, 5.12) years, including 85 boys. Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…We have previously shown systolic BP measured using doppler device to be similar to that measured using auscultation with <1 mmHg difference between the two methods [16]. Using HDBPM, in this study, we observed an average difference of ∼3 mmHg, with home systolic BP values lower than those measured in office using the same technique.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…We have previously shown systolic BP measured using doppler device to be similar to that measured using auscultation with <1 mmHg difference between the two methods [16]. Using HDBPM, in this study, we observed an average difference of ∼3 mmHg, with home systolic BP values lower than those measured in office using the same technique.…”
Section: Discussionsupporting
confidence: 57%
“…Currently, normative data for blood pressure at home is only available for children age 6–18 years using automated oscillometric BP instrument [8], with no normative out-of-office data for children less than 5 years and none using HDBPM. Despite this, as systolic BP measured using HDBPM is similar to auscultatory systolic BP it is relevant and shown to be clinically helpful [16]. Despite the low study numbers, we would contend that our finding of lower than initially estimated difference between Office-SBP Doppler and Home-SBP Doppler , provides further useful data to inform design for a prospective study evaluating agreement between home and office BP for young children.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Reliability of systolic blood pressure measured by parents in young children at home using a hand held Doppler device and aneroid sphygmomanometer: methodological issue to avoid misinterpretation Siamak Sabour a,b I read with great interest the study by Newton et al that published in the J Hypertens 2024 Feb. [1] The purpose of the study was to compare health professional measured office systolic BP by Doppler device (Office-SBP Doppler) with parent measured home systolic BP using the same Doppler device (Home-SBP Doppler). They also report data evaluating reliability.…”
mentioning
confidence: 99%